(untitled) (Social Science Review, 2023)
Global reserves accumulation experienced impressive gains following the late 1990s Asian financial crisis that undermined not only the Asian economies but also the world. Since then, only 49 Asian countries are contributing more than 60% of global hoarding and this trend has been considered from various insights of the international policy agenda. But the logic behind this enormous accumulation is still a matter of serious debate among researchers which is examined in this paper. The empirical estimation based on the unbalanced panel of 49 Asian countries from the period of 1999-2021 confirms precautionary motive as the best illustrator of holding reserves. Asian countries hold reserves as a safeguard against temporary external imbalances and uncertainty in the balance of payment. Against the popular myth that export, or GDP growth has no effect on reserve accumulation. However, exchange rate stability has some effect. Social Science Review, Vol. 40(1), Jun 2023 Page 203-221